Influence of Calcium Salts on Quality and Microstructure of Minimally-processed Litchi Fruit - Putkrong Phanumong (Science Faculty of Chiang Mai University, 2019)
Three different calcium salts (calcium chloride, calcium lactate, and calcium propionate) were used to improve the texture quality and microstructure of minimally-processed litchi fruit (Litchi chinensis cv. ‘Jugkapat’). The pH, titratable acidity (TA), total soluble solids (TSS), pectin methylesterase (PME) and polygalacturonase (PG) activities, the degree of methyl esterification, and scanning electron microscopic observations were studied, immediately after treatment and during storage at 2±1 °C for 12 days. Calcium chloride could reinforce the cell wall and retard the loss of cell turgor at a microscopic level during the storage. The PME activities of the litchi arils treated with calcium salts were higher than the control immediately after treatment (day 0) and throughout the storage. The calcium lactate treatment showed the highest firmness value, especially on the initial days of storage and decreased with further storage. Mitigation of the methyl esterification degree of the cell wall components of the litchi aril might have contributed to the enhanced firmness. Each of the calcium salt treatments decreased the PG activity. Calcium chloride was superior to the other calcium salts, as it slightly changed the aril’s TSS, TA, and pH during storage, with the additional benefit of retarding the TSS/TA decline. Overall, calcium chloride could be a suitable firming agent in maintaining the texture quality of minimally-processed litchi fruit.